TMOD-28. MYC GENERATES AGGRESSIVE MEDULLOBLASTOMA BY HSP90 PATHWAY ACTIVATION AND ARF SILENCING. (12th November 2021) - Mainwaring, Oliver; Weishaupt, Holger; Hutter, Sonja; Zhao, Miao; Borgenvik, Anna; Rosén, Gabriela; Breinschmid, Laura; Verbaan, Annemieke D; Sundström, Anders; Annusver, Karl; Kasper, Maria; Swartling, Fredrik
Abstract: Medulloblastoma, the most common malignant pediatric brain tumor, often shows amplification or overexpression of the MYC transcription factor and arises in the presence of a functional p53 tumor suppressor protein. To elucidate the mechanism behind this inexplicable tumor development we generated an inducible, immunocompetent transgenic mouse model of MYC-expressing medulloblastoma. Aggressive tumors developed clonally in the presence of an unaltered p53 gene that molecularly resembled Group 3 medulloblastoma. Compared to MYCN-expressing medulloblastoma driven from the same promoter, we instead discovered pronounced and MIZ1-independent silencing of the ARF suppressor, which was also suppressed in MYC-amplified as compared to MYCN-amplified human medulloblastoma. While MYCN-driven tumor malignancy was more sensitive to ARF depletion, it dramatically increased metastatic spread of MYC-driven tumors. DNMT inhibition could restore ARF levels in MYC-expressing tumors but did not show any therapeutic advantage in tumors in vivo. Bioinformatics analysis further showed a strong correlation of the HSP90 pathway with MYC in human Group 3 MB and in the MYC-driven mouse model. The HSP90 inhibitor Onalespib showed significant selectivity for targeting MYC-driven as compared to MYCN-driven tumors. The drug promoted ARF restoration and increased the survival in our animal model which suggests that it could be potentially used in the treatment of MYC-driven ARF-silenced brain cancer patients.